The Effect of Japanese Papaya Leaf Powder (Cnidoscolus aconitifolius) as a Natural Preservative of Block Fish During Cold Temperature Storage - Nazaruddin, Muchammad Vishal; Winarti, Sri; Riski Ayu Anggreini (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Mackerel (Rastelliger Sp.) is a small pelagic fish commonly consumed as a source of animal protein. Due to its high susceptibility to spoilage, effective storage and the use of natural preservatives are essential to extend its shelf life. Japanese papaya leaf powder, which contains alkaloids, flavonoids, tannins, and saponins, has potential as a natural preservative due to its antimicrobial properties. This study aims to evaluate the optimal combination of Japanese papaya leaf powder concentration and storage duration on the quality of mackerel stored at low temperatures. A completely randomized factorial design was employed, with two factors: the concentration of Japanese papaya leaf powder (0%, 6%, 8%, and 10%) and storage duration (0, 2, 4, and 6 days). Data were analyzed using ANOVA at a 5% significance level, followed by Duncan's Multiple Range Test (DMRT) at the same significance level. The results indicated that the best treatment combination was 10% Japanese papaya leaf powder and 4 days of storage. This combination yielded a moisture content of 64.51%, a total microbial count of 6.6 cfu/g, a total volatile basic nitrogen (TVBN) level of 23.28 mg/100g, a pH of 5.34, a trimethylamine (TMA) level of 6.15 mg/100g, and a water holding capacity (WHC) of 53.11%. The organoleptic assessment showed that the mackerel maintained acceptable color and aroma, indicating effective preservation.